Distance Learning in Philippine Business Programs: An Action Research for the Delivery of Quality Education Towards Sustainable Community Development - Eunice Mareth Querol Areola, Phd HSG; Joan Camille P Ilagan; Irvin Recto Perono (Journal of Sustainable Community Development (JSCD), 2021)
Education is one of the hardest hit sector of the ongoing global health crisis. Elsewhere, educators continue to grapple with their new reality of balancing content, context and form in order to efficiently deliver online the critical teaching and learning in the business programs. A much-needed clarity for the new direction of education is needed by all academic stakeholders. While governments emphasize a new normal for teaching and learning, every student and educator is left with multiple unanswered questions: how does the virtual community expect to learn? Is it enough to know the best practice of a different country context, or should there be local practices that also deserve to be repeated and amplified? Is the localICT infrastructure sufficient? Are educators equipped with both technical and soft skills? Are students prepared to learn virtually? Do academic institutions have the resources to implement large-scale virtual learning? The adaption for distance learning by the Business programs becomes the center of this action research.